PENYELENGGARAAN BELAJAR DARI RUMAH MASA COVID-19 DI LINGKUNGAN DESA TERPENCIL (DESA CIPANG KANAN) KABUPATEN ROKAN HULU - Dina Purnamasari; Arnita Arnita (Jurnal Ilmu Lingkungan, 2022)
The decision to organize online learning was taken as an alternative to learning during the Covid-19 outbreak emergency so that each individual has a role in breaking the chain of global Covid-19 transmission that spreads to all corners of the world including Indonesia. With schools as one of the most urgent public spaces with the greatest potential to spread or to break the chain of transmission of Covid-19, therefore it is an alternative to carry out the learning process by implementing learning from home and also in concession area. The research data were obtained by interviewing and observing 30 junior high school teachers and Elementary school teachers in the Cipang Kanan village  who were randomly selected. Conclusion The implementation of learning from home for Junior High School Levels and Elementary school Levels  - Cipang Kanan Village, Rokan Hulu Regency did not reach the desired target due to various obstacles, namely learning applications, internet networks and devices, learning management, assessment, and supervision.